FRIEDRICH BRAUELL: LIFE AND RESEARCH - M. V. Trushin (Журнал инфектологии, 2018)
The article, written on the basis of data from the Russian and European archives, is the most complete biography of the famous figure of the Russian medical and veterinary science of the middle of the XIX century Friedrich Brauell, one of the pioneers of anthrax research. The article describes in detail the period of formation of F. Brauell as a scientist – his education received in Germany, visit to the Russian Empire for service, confirmation of academic degree received at homeland. His first steps in the field of teaching and science at Kazan University are discussed in details, his efforts to create a collection of anatomical preparations are described. The main part of the article is devoted to his work in Derpat (Tartu) Veterinary School, where he fully revealed his talent as a major organizer of scientific and educational activities. Particular attention is paid to its study of the problem of anthrax and plague. In addition, the article deals with the issues of his personal life and family for the first time. Thus, the material contained in the article can be useful for scientists studying the history of medicine, infectious diseases and veterinary medicine.